2009
DOI: 10.1007/s11182-010-9363-8
|View full text |Cite
|
Sign up to set email alerts
|

Modified carbon nanostructures as materials for hydrogen storage

Abstract: Within the framework of ab initio simulation, a number of modifications of well-known carbon nanostructures are proposed, which could form the basis for designing materials with high adsorptivity for molecular hydrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…reported that the hydrogen storage could be enhanced by the replacement of carbon atoms in the C 36 fullerene with B . Farther, the B‐doped carbon systems with subsequent Li metal doping in carbon nanotube have been investigated in relation to hydrogen storage . Aromatic carbon‐ring molecular materials decorated with alkali or alkaline earth metals for hydrogen storage capacity have been theoretically investigated by Bodrenko et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that the hydrogen storage could be enhanced by the replacement of carbon atoms in the C 36 fullerene with B . Farther, the B‐doped carbon systems with subsequent Li metal doping in carbon nanotube have been investigated in relation to hydrogen storage . Aromatic carbon‐ring molecular materials decorated with alkali or alkaline earth metals for hydrogen storage capacity have been theoretically investigated by Bodrenko et al .…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al reported that the hydrogen storage could be enhanced by the replacement of carbon atoms in the C 36 fullerene with B [39]. Farther, the B-doped carbon systems with subsequent Li metal doping in carbon nanotube have been investigated in relation to hydrogen storage [40,41]. Aromatic carbon-ring molecular materials decorated with alkali or alkaline earth metals for hydrogen storage capacity have been theoretically investigated by Bodrenko et al [42] In addition, the hydrogen storage capacity of alkali and alkali earth metal ions that doped carbon-based materials such as cubane, cyclohexane, and adamantine has been studied using a density functional theory by Gopalsamy and Subramanian [43].…”
Section: Introductionmentioning
confidence: 99%
“…39 Further, the boron-doped carbon systems with Li metals coating in carbon nanotube has been studied with regard to hydrogen storage. 40,41 Hydrogen storage capacity in aromatic carbon ring molecular materials decorated with alkali or alkaliearth metals has been theoretically studied by Bodrenko et al 42 In addition, Gopalsamy and Subramanian carried out a density functional theory calculation on the hydrogen storage capacity of alkali and alkali-earth metal ions doped carbon based materials such as cubane, cyclohexane, and adamantine. 43 In the present work, we chose the carbon ring, benzene, as the studying model.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, boron, gaining an extra electron from a metal atom, can acquire properties similar to carbon [15,16]. More specifically, hydrogen molecules are attracted to the field via dispersion interaction [17,18]. Such construction allows harnessing electrostatic field created by positive metal and negative boron ions.…”
Section: Introductionmentioning
confidence: 99%
“…Such construction allows harnessing electrostatic field created by positive metal and negative boron ions. More specifically, hydrogen molecules are attracted to the field via dispersion interaction [17,18]. On the other hand, this electrostatic interaction increases metal-support interaction that prevents metal atoms from clustering [6].…”
Section: Introductionmentioning
confidence: 99%